Bright ultrashort echo time SWIFT MRI signal at the osteochondral junction is not located in the calcified cartilage. Issue 12 (1st July 2020) - Nykänen, Olli; Leskinen, Henri P. P.; Finnilä, Mikko A. J.; Karhula, Sakari S.; Turunen, Mikael J.; Töyräs, Juha; Saarakkala, Simo; Nissi, Mikko J.
Abstract: In this study, we aimed to precisely localize the hyperintense signal that is generated at the osteochondral junction when using ultrashort echo time magnetic resonance imaging (MRI) and to investigate the osteochondral junction using sweep imaging with Fourier transformation (SWIFT) MRI. Furthermore, we seek to evaluate what compositional properties of the osteochondral junction are the sources of this signal. In the study, we obtained eight samples from a tibial plateau dissected from a 68‐year‐old male donor, and one additional osteochondral sample of bovine origin. The samples were imaged using high‐resolution ultrashort echo time SWIFT MRI and microcomputed tomography (μCT) scans. Localization of the bright signal in the osteochondral junction was performed using coregistered data sets. Potential sources of the signal feature were examined by imaging the bovine specimen with variable receiver bandwidths and by performing variable flip angle T1 relaxation time mapping. The results of the study showed that the hyperintense signal was found to be located entirely in the deep noncalcified articular cartilage. The intensity of this signal at the interface varied between the specimens. Further tests with bovine specimens indicated that the imaging bandwidth and T1 relaxation affect the properties of the signal. Based on the present results, the calcified cartilage has low signal intensity even in SWIFT imaging. Concomitantly, it appears that the bright signal seen in ultrashort echo time imaging resides within the noncalcified cartilage. Furthermore, the most likely sources of this signal are the rapid T1 relaxation of the deep cartilage and the susceptibility‐induced effects arising from the calcified tissues.